More Schooling, Less Youth Crime? Learning from an Earthquake in Japan - Yu Aoki (Institute for the Study of Labor (IZA), 2014)
This paper aims to identify the causal effect of schooling on youth crime. To identify the causal effect, I use the policy interventions that occurred after the Kobe earthquake that hit Japan in 1995 as a natural experiment inducing exogenous variation in schooling. Based on a comparison of the arrest rates between municipalities exposed to similar degrees of earthquake damage but with and without the policy interventions, I find that a higher high school participation rate reduces juvenile arrest rates for violent crime but not for property crime. The estimates of social benefits show that it is less expensive to reach a target level of social benefits by improving schooling than by strengthening the police force.
Keywords: H52; I28; K42; 330; schooling; youth crime; social externality